2018
DOI: 10.1016/j.jfda.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Compositional analyses of white, brown and germinated forms of popular Malaysian rice to offer insight into the growing diet-related diseases

Abstract: Diet-related metabolic diseases, and especially obesity, are metabolic disorders with multifactorial aetiologies. Diet has been a cornerstone in both the aetiology and management of this metabolic disorders. Rice, a staple food for over half of the world's population, could be exploited as part of the solution to check this menace which has been skyrocketing in the last decade. The present study investigated nine forms of rice from three widely grown Malaysian rice cultivars for in vitro and in vivo (glycaemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 25 publications
5
22
1
1
Order By: Relevance
“…Also, BR showed a greater bioactive content compared to WR, but lower than that of GBR. In addition, the content of phenolics varied depending on rice cultivar (Abubakar, Yakasai, Zawawi, & Ismail, ). Another recent study found that the bound fraction is the main phytochemicals component in glutinous and nonglutinous BR varieties (Gao et al., ).…”
Section: Potential Health Benefitsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, BR showed a greater bioactive content compared to WR, but lower than that of GBR. In addition, the content of phenolics varied depending on rice cultivar (Abubakar, Yakasai, Zawawi, & Ismail, ). Another recent study found that the bound fraction is the main phytochemicals component in glutinous and nonglutinous BR varieties (Gao et al., ).…”
Section: Potential Health Benefitsmentioning
confidence: 99%
“…Also, antioxidant activity of BR or its extracts is influenced by pretreatments or processing. For example, GBR derived extracts showed a higher antioxidant activity than that of BR or WR extract (Abubakar et al., ; Cho & Lim, ; Mohd Esa, Abdul Kadir, Amom, & Azlan, ; Ti et al., ). The increase in antioxidant activity of GBR could be attributed to that germination enhances the content of bioactive compounds.…”
Section: Potential Health Benefitsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Ali, ). Brown rice (BR) is a good choice for a healthy diet because it has a higher nutritive value and antioxidant activity as well as numerous other benefits as opposed to white rice (Abubakar, Yakasai, Zawawi, & Ismail, ; Pang et al. ).…”
Section: Introductionmentioning
confidence: 99%